Memori Verbal Sebagai Prediktor Kemampuan Bahasa Lisan Pada Anak-Anak Prasekolah - Yusi Lusia Ningsih; Rexsy Taruna (Jurnal Terapi Wicara, 2023)
This study aims to assess how much the predictive power of verbal short term memory has on language skills. Participants in this study involved 50 typical preschool children, with a range of ages four to six years. Each participant was assessed using the Test of Auditory Processing Skill (TAPS-3) and Developmental Profile (DP-3). Data analysis in this study used correlation tests and linear regression tests with JASP. The results showed that there was a significant relationship between verbal short term memory and language skills (r = 0.635; p <0.001).